2014
DOI: 10.1186/1746-1596-9-3
|View full text |Cite
|
Sign up to set email alerts
|

Combination of conventional immunohistochemistry and qRT-PCR to detect ALK rearrangement

Abstract: Background: Compared with FISH and qRT-PCR analyses, immunohistochemistry (IHC) is the preferred screening test in most pathology practices for ALK-rearrangement detection. With 100% sensitivity and 98% specificity, the VENTANA ALK (D5F3) IHC assay has been approved in the EU and some Asian countries for ALK-rearrangement detection. However, an automated Ventana IHC platform is not available in most pathology labs. In this study, we evaluated the applicability of conventional IHC with D5F3 antibody in routine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 23 publications
1
57
1
Order By: Relevance
“…The incidence of ALK rearrangements was found to be 9.6% (73/763) in NSCLC and 11.0% (54/493) in adenocarcinoma in our study, which was similar to the results previously published in Chinese (Shan et al, 2014;Wang et al, 2014a;Yang et al, 2014) and Asian cohorts (Kim et al, 2014). As previously reported, patients who were ALK-positive were predominantly young women and never/light smokers (Lynch et al, 2004;Rodig et al, 2009;Shaw et al, 2009;Wong et al, 2009;Jokoji et al, 2010;Takahashi et al, 2010;Zhang et al, 2013;Zhang et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The incidence of ALK rearrangements was found to be 9.6% (73/763) in NSCLC and 11.0% (54/493) in adenocarcinoma in our study, which was similar to the results previously published in Chinese (Shan et al, 2014;Wang et al, 2014a;Yang et al, 2014) and Asian cohorts (Kim et al, 2014). As previously reported, patients who were ALK-positive were predominantly young women and never/light smokers (Lynch et al, 2004;Rodig et al, 2009;Shaw et al, 2009;Wong et al, 2009;Jokoji et al, 2010;Takahashi et al, 2010;Zhang et al, 2013;Zhang et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Recently many studies have reported the efficacy of Ventana IHC for detecting ALK rearrangements with D5F3 antibodies and have supported that Ventana IHC is a method with excellent sensitivity and specificity to identify ALK rearrangements in paraffin-embedded lung cancer specimens (Takahashi et al, 2010;Zhang et al, 2013;Shan et al, 2014;Wang et al, 2014a;Zhang et al, 2014). The sensitivity and specificity of Ventana IHC were found to be 100 and 98.2%, respectively, and the concordance rate between the fluorescence in situ hybridization (FISH) and the Ventana IHC was 98.4% (Wang et al, 2014a).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This assay has been approved for ALK-rearrangement detection by the FDA in China and Taiwan. [23][24][25] From the…”
Section: Discussionmentioning
confidence: 99%